Board Gender Diversity and Its Risk Monitoring Role: Is it Significant? - Karren Lee-Hwei Khaw; Jing Liao (Asian Academy of Management Journal of Accounting and Finance, 2018)
In recent years, there is an urgent call to strengthen board composition to safeguard against expropriation of shareholders’ interest and to reinforce public confidence, specifically in a weaker governance setting. Board gender diversity receives considerable attention within the issues of corporate governance. This is because female directors are found to be more active in monitoring activities, cautious in decision making, less aggressive and risk averse as compared to male directors. We support this argument with evidence from a sample of listed firms in Malaysia. In line with the literature, we show that female directors play a significant monitoring role in reducing corporate risk taking behaviour. Our results are robust to endogeneity concern. Since board gender diversity plays a significant risk monitoring role, we recommend that there should be a continuous call to appoint female directors to the boardrooms among Malaysian listed firms to diversify the ‘old boys club’ corporate boardrooms.